2017
DOI: 10.1002/2017jd027007
|View full text |Cite
|
Sign up to set email alerts
|

Western North Pacific Tropical Cyclone Model Tracks in Present and Future Climates

Abstract: Western North Pacific tropical cyclone (TC) model tracks are analyzed in two large multimodel ensembles, spanning a large variety of models and multiple future climate scenarios. Two methodologies are used to synthesize the properties of TC tracks in this large data set: cluster analysis and mass moment ellipses. First, the models' TC tracks are compared to observed TC tracks' characteristics, and a subset of the models is chosen for analysis, based on the tracks' similarity to observations and sample size. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 111 publications
4
61
0
Order By: Relevance
“…For example, some model simulations suggest an increase in the global 16,17 and western North Pacific 18,19 TC frequency under a warmer climate. Nakamura et al 20 showed through multi-model analyses that there is a large range of uncertainty across numerical simulations as to whether a poleward shift of TC occurrence exists in the western North Pacific basin, where there has been the largest trend in the observations for the lifetime maximum intensity of TCs 21 and TC genesis location 22 , although the combined multimodel signal has a statistically significant poleward shift in a warmer climate. In the North Atlantic, Daloz et al 23 did not find any significant TC track changes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some model simulations suggest an increase in the global 16,17 and western North Pacific 18,19 TC frequency under a warmer climate. Nakamura et al 20 showed through multi-model analyses that there is a large range of uncertainty across numerical simulations as to whether a poleward shift of TC occurrence exists in the western North Pacific basin, where there has been the largest trend in the observations for the lifetime maximum intensity of TCs 21 and TC genesis location 22 , although the combined multimodel signal has a statistically significant poleward shift in a warmer climate. In the North Atlantic, Daloz et al 23 did not find any significant TC track changes in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This setting is called ''Ubeta0.'' A recent study by Nakamura et al (2017) shows a systematical north-northeast-ward track bias in Emanuel's data set in the WPC. Such bias might be related to the zero beta drift, which prevents westward moving tracks.…”
Section: Track-beta-advection Model (Bam)mentioning
confidence: 91%
“…In the first experiment, we set boldVboldβ = (0.0, 2.5) following Emanuel et al (), that is, zero beta drift in the zonal direction and 2.5 m s −1 in the meridional direction. This setting is called “Ubeta0.” A recent study by Nakamura et al () shows a systematical north‐northeast‐ward track bias in Emanuel's data set in the WPC. Such bias might be related to the zero beta drift, which prevents westward moving tracks.…”
Section: Development Of Individual Model Componentsmentioning
confidence: 99%
“…Warming temperatures and shifting precipitation regimes will drive increases in the fire season length [53] and intensify drought severity [37,39]. While projections vary on changes in Pacific tropical cyclogenesis frequency [54,55], tropical cyclones are expected to undergo a poleward shift [55] that may favor increases in eventual North American landfall. Future contributions of remnant typhoon moisture to early water year precipitation could become more important in relieving drought conditions and mitigating wildfire hazard along the west coast of North America, both of which have positive impacts for ecosystems and human life and property.…”
Section: Discussionmentioning
confidence: 99%